Vaginal Lactobacilli Induce Differentiation of Monocytic Precursors Toward Langerhans-like Cells: in Vitro Evidence - Song, Jie; Lang, Fengchao; Zhao, Na; Guo, Yan; Zhang, Huatang (Frontiers in Immunology, 2018)
Lactobacilli have immunomodulatory mechanisms that affect the host cell immune system, leading to inhibition of HIV-1 transmission. Thus, lactobacilli as mucosal delivery vehicles for developing HIV-1 vaccines have attracted interest in recent years. Herein, we investigated the immunomodulatory effects of six strains of Lactobacillus naturally isolated from vaginal samples, including Lactobacillus crispatus (L. crispatus), L. fermentum, L. jensenii, L. gasseri, L. delbrueckii and L. johnsonii, on differentiation of monocytic precursors. L. crispatus, L. fermentum and L. delbrueckii could drive human monocytic cell line THP-1 cells to differentiate into dendritic-like cells according to the morphology. Moreover, L. crispatus increased costimulatory molecules including CD40, CD80 and CD86, and Langerhans cell specific C-type lectin receptors CD207, while L. fermentum decreased these molecules in THP-1 cells. Furthermore, L. crispatus promoted the differentiation of THP-1 cells with specific markers, phagocytic features, cytokine production ability and reduced the expression of receptors for HIV-1 entry of Langerhans cells. However, in the presence of L. fermentum, THP-1 cells did not show the above alterations. Moreover, similar effects of L. crispatus and L. fermentum were observed in CD14+ monocytes. These data suggested that L. crispatus facilitates the differentiation of monocytic precursors towards Langerhans-like cells in vitro. We further identified the cell wall components of Lactobacillus and found that peptidoglycans (PGNs), rather than bacteriocins, S-layer protein and lipoteichoic acid, were key contributors to the induction of CD207 expression. However, PGNs originating from Bacillus subtilis, E. coli JM109 and E. coli DH5α did not elevate CD207 expression, indicating that only PGN derived from Lactobacillus could enhance CD207 expression. Finally, the recognized receptors of L. crispatus (such as TLR2 and TLR6) and the upstream transcription factors (PU.1, TAL1, TIF1γ and POLR2A) of CD207 were examined, and the expression of these molecules was enhanced in THP-1 cells following L. crispatus treatment. Thus, this study offers powerful evidence that vaginal lactobacilli modulate monocytic precursor differentiation into Langerhans-like cells probably via activating the TLR2/6-TFs-CD207 axis. These data provide clues for further investigation of the original occurrence, development and differentiation of Langerhans cells from monocytes.